Cover Feature: Unprecedented Mechanism of an Organocatalytic Route to Conjugated Enynes with a Junction to Cyclic Nitronates (Eur. J. Org. Chem. 2‐3/2019). Issue 2 (27th December 2018) - Streitferdt, Verena; Haindl, Michael H.; Hioe, Johnny; Morana, Fabio; Renzi, Polyssena; von Rekowski, Felicitas; Zimmermann, Alexander; Nardi, Martina; Zeitler, Kirsten; Gschwind, Ruth M.
Abstract : The Cover Feature shows a machine that generates conjugated enynes and cyclic nitronates within a one‐pot reaction from simple nitroalkenes. The reaction towards both products shares a common pathway that deviates towards enynes or nitronates depending on the reaction conditions. By adjusting additive and base, the selectivity between enynes and nitronates can be controlled. NMR reaction monitoring in combination with theoretical calculations helped to elucidate the mechanism towards both products. This machine stands as a symbol for reaction flasks or NMR‐tubes in which the reactions were carried out. More information can be found in the Full Paper by R. M. Gschwind et al.